The Recovery-Based Interprofessional Distance Education (RIDE) Rotation: Content and Rationale. (3rd October 2015) - Beebe, Lora; Raynor, Hollie; Roman, Marian W.; Thompson, Dixie; Ray, Shaunta
Abstract : A faculty team of two psychiatric nurse practitioners, an exercise physiologist, a registered dietician and a pharmacist developed the 8-week Recovery-Based Interprofessional Distance Education (RIDE) rotation for graduate students in the four disciplines. Organizing the RIDE rotation around the recovery model ensured an emphasis upon optimal health and quality of life. RIDE faculty engaged in project planning for several months before the RIDE rotation was offered to students. In this paper, we describe details of the 8-week program. Our next step will be to analyze student feedback and de-identified evaluation data from the first student cohort.